IMPLEMENTASI ONLINE ANALYTICAL PROCESSING (OLAP) PADA STUDI KASUS SISTEM INFORMASI MANAJEMEN PERIJINAN MENGGUNAKAN ALAT BANTU MICROSOFT BUSINESS INTELLIGENCE DEVELOPMENT STUDIO - Dimara Kusuma Hakim (Universitas Muhammadiyah Purwokerto, 2011)
Business licensing data in a district that has been collected in a database, it would be very useful when analyzed, so a lot of important information is obtained. The need of data reporting types is endless in accordance with the needs of organization. It makes organization depends on application developer to make report, therefore, they need a system that can analyze data easily. Online Analytical Processing (OLAP) is an implementation of Datawarehousing that can help reporting and analysis well. OLAP can map the data with cube dimensions, each cube can be easily compared, so decision maker can easily and quickly to find the suspected cause of the problems that faced. Kata Kunci:OLAP, Data Warehouse, Permit Application, Microsoft Business Intelligence Development Studio